Compressive local buckling of integrated fluted-core sandwich composite panels. (September 2021) - Li, Xinyu; Lei, Hongshuai; Yang, Haiyang; Wang, Huiping; Zhang, Zhong; Zhang, Hao; Chen, Haosen
Abstract: Fluted-core sandwich structures, consisting of fiber-reinforced plastics, are frequently utilized in the aerospace industry owing to their excellent strength-to-weight ratio. However, the thin-walled structures are prone to local buckling, which reduces their load-bearing capacity and eventually leads to material failure. The current study presents analytical models for predicting the local buckling of fluted-core sandwich panels subjected to uniform compressive load. The proposed method is based on a discrete plate analysis approach, which considers the face-sheets between two webs as rotationally-restrained plates, wherein the rotational restraint stiffness is determined based on the geometric configuration and material properties. Herein, two boundary conditions, i.e., simply-supported and clamped, along the loaded edges were studied. Several deflection functions were proposed based on the classical Rayleigh–Ritz method, satisfying the boundary conditions. The experimental tests and finite element simulations were carried out to analyze the local buckling behavior, rendering excellent consistency and demonstrating the reliability of the proposed method. The effects of geometric parameters on the local buckling behavior were systematically studied and the results revealed that the current analytical models with high computational efficiency are reliable, exhibiting promise of eventual success in the optimization of preliminary engineering designs. Highlights: Local buckling analysis of the fluted-core composite panels was presented. The buckling of rotationally-restrained plates was studied using Rayleigh–Ritz method. Compressive local buckling behaviors were explored by experiment and FEA methods. Effects of geometric parameters on local buckling behavior were discussed.